Effect of shading and growing season on the agronomic performance of jambu - Silva, Andressa de Oliveira; Barral, Deiviane de Souza; Do Rosário, Isabelle Caroline Bailosa [UNESP]; Santos, Lucas da Silva; Gomes, Rafaelle Fazzi (FapUNIFESP (SciELO), 2023)
The jambu (Acmella oleracea) production can be influenced by the growing season and light available for metabolic processes. This study aimed to assess the agronomic and physiological performance of two jambu varieties, under different shading levels, during the winter and summer of the Brazilian Amazon. Two random block experiments were conducted, in a 2 x 4 factorial scheme, consisting of two jambu varieties (yellow and purple flower) and four shading levels (0, 30, 50 and 70 %), with four replications. Physiological, growth and yield traits were assessed. There was no significant interaction between treatments and growing seasons (Amazon winter and summer) for growth or yield traits, nor between treatments for the physiological characteristics. The cultivation without shading screen can increase the shoot dry weight of both varieties; the yellow flower variety exhibited early-onset flowering regardless of the shading screen used; the “Amazon summer” growing season increased the jambu yield by 33 %, while the 70 % shading reduced the net photosynthetic rate, consequently not favoring the vegetative development of the jambu plants. As such, it is recommended that the yellow and purple flower jambu varieties be grown without shading screen in the Amazon summer.
Sombreamento e época de cultivo no desempenho agronômico de jambu
Keywords: Acmella oleracea [L.] R. K. Jansen; Amazon; unconventional food plant